Aggregate Investment Expenditures on Tradable and Nontradable Goods - Bems, Rudolfs (IMF Working Papers; Working Paper, 2008)
This paper shows that aggregate investment expenditure shares on tradable and nontradable goods are very similar across countries and regions. Furthermore, the two expenditure shares have remained close to constant over time, with the average expenditure share on nontradables varying between 0.54-0.62 over the 1960-2004 period. These empirical findings offer a new restriction for two-sector models of the aggregate economy. Combined with the fact that the relative price of nontradables correlates positively with income and exhibits large differences across space and time, our findings suggest that tradable and nontradable goods in investment can be modeled using the Cobb-Douglas aggregator.